Workers into Managers: Developing Leadership Competence of Production Unit Managers - Christoph Rappe; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This study analyses the competence gaps of lower-level managers in a typical manufacturing plant in Germany that had recently introduced a teamwork structure. Results indicate that the managers have difficulties with their new leadership-related tasks. Higher levels of leadership competence are found to be associated with better acceptance as a manager by superiors, but not by subordinates, better interaction with both subordinates and superiors, and with higher job satisfaction. Finally, a quasi-experiment shows that a combination of workshops and individual coaching had measurable effects on leadership competencies and partly improved identification with the managerial role. In terms of methodology, a new format of self-assessments is suggested for a more valid measurement of competencies.
Keywords: J24; C93; M12; 330; Leadership skills; first line managers; training; experiment; Gruppenarbeit; Führungspersönlichkeit; Facharbeiter